The Role of Literary Form in Plato's Dialogues - Houlding , Joan (My University, 1985)
This work on the role of literary form in Plato's dialogues is in response to the problem set by different approaches to an understanding of Platonic thought. The traditional approach to the study of Plato attempts to separate literary form, considered an irrelevant element, from philosophic content. A second kind of approach views each dialogue as a dramatic whole. Here, philosophic content is one component of the whole and literary form is considered to be of primary importance. A third approach attempts to give equal consideration to literary form and philosophic content. In this thesis, I examine the role of literary form in the Phaedrus in Chapter Two and in the Republic in Chapter Three. In Chapter Four, general patterns of form recognizable in the Euthyphro and the Philebus are assessed. My claim is that full access to an understanding of Plato is achieved only when both aspects, form and content, are recognized as integral aspects of the whole. I argue that literary form is an integral element in the totality of Plato's thought.
Keywords: Plato; Literary form